Hygienic quality, study of enterobacteria isolated from table olives and antimicrobial activity of Olea europaea L from Tetouan, Morocco - Mennane Zakaria (EDP Sciences, 2021)
88 samples of traditional and industrial table olives were collected from various outlets in the city of Tetouan. The physical-chemical controls concerned: pH , ORP (oxydo-reducing potential) and TDE (total dry extract). The microbiological side are: total aerobic mesophilic flora ( TAMB), total coliforms (TC), Staphylococcus aureus (SA) and lactic bacteria (LB) with an identification of the most predominant enterobacteria species and their sensitivity. Also to investigate the antimicrobial activity of Olive (Olea europaea L.) .The obtained results for traditional olives far exceed food hygiene standards, especially when 29.20% of traditional samples are too loaded in TAMB and TC and 16.5% are contaminated with SA. This shows that good hygiene practices are not respected. As for industrial olives, the averages in TAMB and SA are below the thresholds set by the standards, and only 19.8% are contaminated with TC which indicates the compliance of the majority of industrial type. Black table olives are the most contaminated. The identification results of coliforms extracted from traditional olives show the predominance of Citrobacter freundii and klebsiella pneumoniae .The sensitivity test shows that 80% of Enterobacteriaceae tested were sensitive to all antibiotics.The result showed that the ethanolic extrats was active against all bacteria.